Nitrite reverses nitroglycerin tolerance via repletion of a nitrodilator-activated nitric oxide store in vascular smooth muscle cells - Taiming Liu; Meijuan Zhang; Qian Li; Hobe Schroeder; Gordon G. Power; Arlin B. Blood (Redox Biology)
Repeated use of nitroglycerin results in a loss of its vasodilatory efficacy which limits its clinical use for the treatment of angina pectoris. This tolerance phenomenon is a defining characteristic of all compounds classified as nitrodilators, which includes NTG as well as S-nitrosothiols and dinitrosyl iron complexes. These compounds vasodilate via activation of soluble guanylate cyclase, although they do not release requisite amounts of free nitric oxide (NO) and some do not even cross the plasma membrane. Here we demonstrate that nitrodilators cause vasodilation via mobilization of NO moiety from a nitrodilator-activated NO store (NANOS) pre-formed in the vascular smooth muscle cell, similar to the mechanism by which UV light is also known to cause vasodilation and tolerance. Intraperitoneal nitrite prevented NTG tolerance in coronary arteries of rats that received NTG transdermal patches for 4 days, and potentiated NTG- and GSNO- mediated mesenteric vasodilation in intact rats. Consistent with the incorporation of nitrite into the depletable NANOS, incubation of arteries with 15N-nitrite resulted in the accumulation of high molecular weight 15N–NO-containing compounds in arteries, and subsequent exposure to NTG, GSNO, or UV light resulted in efflux of 15N–NO species. In addition, H2O2 and metal/metalloproteins synergistically facilitated NO release from nitrite, while the oxidative stress associated with inflammation and nitrite synergistically potentiated the nitrodilator-mediated vasodilation. In conclusion, NTG mediates vasodilation via activation of a depletable intracellular store of NO that can be replenished by nitrite, thereby preventing tolerance.